2021
DOI: 10.1007/s00126-021-01067-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a hydrothermal ore-forming system recorded by sulfide mineral chemistry: a case study from the Plaka Pb–Zn–Ag Deposit, Lavrion, Greece

Abstract: Laser ablation-inductively coupled plasma-mass spectrometry and electron-probe microanalysis were used to investigate the trace-element contents of sphalerite, chalcopyrite and pyrite from the Plaka Pb–Zn–Ag deposit. Using petrographic observations, the analytical results could be linked to the temporal evolution of the Plaka ore-forming system. Sphalerite chemistry reliably records the temperature and fS2 evolution of the system, with estimated formation temperatures reproducing the microthermometric results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…9h and ESM 2 Table S4). This is consistent with previous studies that showed the direct substitution of Hg 2+ for Zn 2+ is facilitated in Fe-poor sphalerite that is in turn associated with relatively low-temperature fluid conditions (Grammatikopoulos et al 2006;Keith et al 2014;Frenzel et al 2022). However, this contrasts with sphalerite from the sulfide-rich chimneys that have decreased Hg concentrations from stage I to stage II (Fig.…”
Section: Effect Of Seawater Mixingsupporting
confidence: 92%
“…9h and ESM 2 Table S4). This is consistent with previous studies that showed the direct substitution of Hg 2+ for Zn 2+ is facilitated in Fe-poor sphalerite that is in turn associated with relatively low-temperature fluid conditions (Grammatikopoulos et al 2006;Keith et al 2014;Frenzel et al 2022). However, this contrasts with sphalerite from the sulfide-rich chimneys that have decreased Hg concentrations from stage I to stage II (Fig.…”
Section: Effect Of Seawater Mixingsupporting
confidence: 92%
“…Note: GGIMF is a temperature calculation method cited from Frenzel et al, 2016Frenzel et al, , 2022 content of In in sphalerite from the Dengjiashan deposit was 0.3 ppm, which is similar to that of a SEDEX-type Pb-Zn deposit, considering the geological as well as the aforementioned characteristics of this deposit type.…”
Section: Mineralization Temperaturementioning
confidence: 66%
“…According to the characteristic elements in single minerals or mineral pairs in the coexisting phase, the content, ratio and distribution coefficient of the trace elements are calculated and determined in order to obtain the geological thermometer (Liu et al, 1984;Zheng, 1986). The composition of trace elements in sphalerite is closely linked to its formation temperature (Frenzel et al, 2016(Frenzel et al, , 2022Möller, 1987). Under hightemperature conditions, the activity (vibration) range of atoms is relatively high, and the four-coordinated ionic radii of Fe 2+ (0.63 Å), Mn 2+ (0.66 Å), In 3+ (0.62 Å), and Zn 2+ (0.60 Å) are close to each other.…”
Section: Mineralization Temperaturementioning
confidence: 99%
See 2 more Smart Citations